Pike River [videorecording (DVD)] - Samuel, Fiona; Lynskey, Melanie; Malcolm, Robyn (Brainstorm Media, 2026)
The incredible true story of two women whose friendship empowered them to fight for justice after the Pike River Mine Tragedy took the lives of 29 men underground.